2011
DOI: 10.1371/journal.pone.0027490
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Mediates Cross-Talk between K-Ras and Let-7c Tumor Suppressor microRNA

Abstract: BackgroundGalectin-3 (Gal-3) and active (GTP-bound) K-Ras contribute to the malignant phenotype of many human tumors by increasing the rate of cell proliferation, survival, and migration. These Gal-3-mediated effects result from a selective binding to K-Ras.GTP, causing increased nanoclustering in the cell membrane and leading to robust Ras signaling. Regulation of the interactions between Gal-3 and active K-Ras is not fully understood.Methods and FindingsTo gain a better understanding of what regulates the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 40 publications
(84 reference statements)
1
29
1
1
Order By: Relevance
“…They were grown to a confluency of 80% (8 ϫ 10 7 cells/ml) and subcultured every 2-3 days. Gal-1 Ϫ/Ϫ MEFs were a kind gift from the laboratory of Prof. Yoel Kloog (35). For Western blotting analysis and fluorescence recovery after photobleaching (FRAP) experiments, 200,000 cells were seeded in a 6-well plate (Cellstar catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…They were grown to a confluency of 80% (8 ϫ 10 7 cells/ml) and subcultured every 2-3 days. Gal-1 Ϫ/Ϫ MEFs were a kind gift from the laboratory of Prof. Yoel Kloog (35). For Western blotting analysis and fluorescence recovery after photobleaching (FRAP) experiments, 200,000 cells were seeded in a 6-well plate (Cellstar catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps the best example of Galectin 3 regulation of signal transduction involves RAS (86)(87)(88)(89)(90)(91)(92). (86,89).…”
Section: Galectin 3 Role In Regulation Of Signal Transductionmentioning
confidence: 99%
“…In our studies , we have observed leukemia cells can also induce Galectin 3 in MSC suggesting that the induction of Galectin 3 between cells can be mutual (Ruvolo et al unpublished).Galectin 3 Intracellular functionsGalectin 3 as an anti-apoptotic moleculeGalectin 3 can function as an anti-apoptotic molecule(19,(27)(28)(29)(30)(77)(78)(79)(80)(81)(82)(83). Galectin 3 influences many diverse signal transduction cascades and pro-survival processes that include major oncogenes such as RAS, BCL2, and MYC(19,(27)(28)(29)(30)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92). The tumor suppressor function of anti-apoptotic function is important in some cancer cells(85,(93)(94)(95)(96).…”
mentioning
confidence: 99%
“…Extracellularly, galectins interact with cell surface glycoconjugates and trigger cellular signaling to control migration, immunity, and angiogenesis. Intracellularly, galectins can control tumor transformation, proliferation, and survival (7,8).…”
Section: Introductionmentioning
confidence: 99%